2023
DOI: 10.3389/fonc.2023.1099384
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of preoperative neutrophil-to-lymphocyte ratio in surgically resected schwannomas

Abstract: ObjectiveThe goal of schwannoma resection is to control the tumor while preserving neurological function. Schwannomas have a variable postoperative growth pattern, therefore preoperative prediction of a schwannoma’s growth pattern is favorable. This study aimed to examine the relationship between preoperative neutrophil-to-lymphocyte ratio (NLR) and postoperative recurrence and retreatment in patients with schwannoma.MethodsWe retrospectively examined 124 patients who underwent schwannoma resection in our inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The preoperative NLR index has been reported to reduce the prediction of overall survival (OS) and progression-free survival (PFS) in patients with advanced tumors (5). The NLR >/= 2.2 before surgery has been reported to be significantly associated with retreatment after schwannoma resection (7). The high level of PLR was correlated with poor survival time (10), the results demonstrating a significant correlation between elevated PLR and poor prognosis in UC ( 11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The preoperative NLR index has been reported to reduce the prediction of overall survival (OS) and progression-free survival (PFS) in patients with advanced tumors (5). The NLR >/= 2.2 before surgery has been reported to be significantly associated with retreatment after schwannoma resection (7). The high level of PLR was correlated with poor survival time (10), the results demonstrating a significant correlation between elevated PLR and poor prognosis in UC ( 11).…”
Section: Discussionmentioning
confidence: 99%
“…An immunosuppressive state can occur owing to chronic inflammation and malnutrition, increasing the risk of infection and death in patients with chronic diseases. In recent years, multiple studies have reported the role of peripheral blood biomarkers such as the preoperative neutrophil-to-lymphocyte ratio (NLR) (5)(6)(7)(8)(9), platelet-to-lymphocyte ratio (PLR) (10)(11)(12), lymphocyte-tomonocyte ratio (LMR) (13)(14)(15), and prognostic nutritional index (PNI) (16)(17)(18)(19)(20) to explore the relationship between the physiological and disease status and predict disease-free survival (DFS) in patients with cancer to some extent. The prognosis of breast cancer is intricately associated with inflammation.…”
Section: Introductionmentioning
confidence: 99%